Stretchable and transparent nanopillar arrays for high-performance ultra-flexible organic photovoltaics - Kim, Jae Hyun; Park, Byoungwook; Song, Seulki; Ahn, Junyong; Jeong, Jaebin; Nam, Sang Hyeon; Lee, Seung Hoon; Park, Junyong; Park, Sungjun (Applied Physics Letters, 2024)
Ultra-flexible organic photovoltaic (OPV) devices are gaining recognition due to their lightweight, mechanical flexibility, and high productivity potential and are emerging as a notable alternative power source. Significant enhancements in material design and device architecture have facilitated a near 20% of power conversion efficiencies (PCEs). To elevate PCE further, the integration of soft optical elements is pivotal, enabling optimized photon utilization by minimizing reflection and augmenting the optical path through diffraction. In this research, we showcase an ultra-flexible energy harvesting system embedding thin, stretchable nanopillar arrays made of poly(dimethylsiloxane). The unique diffraction and interference from nanopillar arrays amplify the photogeneration of exciton pairs, which, in turn, boosts the current density of PM6:Y6 based OPV devices from 25.46 to 28.01 mA/cm2, resulting in a PCEmax of 15.92%. Furthermore, the exceptional flexibility of this mold was demonstrated on an ultra-flexible PM6:Y6 device, enduring 100% compressive strain through 1000 repeated tests. These results propose an advantageous approach for improving OPV efficiency without necessitating alterations to the inherent components or structures of the device.
Keywords: Alternative power; High productivity; Materials design; Mechanical flexibility; Nanopillars array; Organic photovoltaic devices; Organic photovoltaics; Performance; Power conversion efficiencies; Power sources